2019
DOI: 10.15414/jmbfs.2019.8.5.1194-1197
|View full text |Cite
|
Sign up to set email alerts
|

Associative to Triticum Aestivum L. Bacteria as a Source of Strains for Biotechnology of the Rhizosphere

Abstract: Associative microorganisms live in the zone of direct influence of plants namely in the soil, which is in close contact with the roots. They form complex communities on the roots of plants in terms of taxonomic composition and structural and functional o8rganization, which have polyfunctional effect on plants. Rhizosphere biotechnologies with the use of associative bacteria to a specific plant species allow increasing their productivity and quality, which contributes to the stability of agroecosystems. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
1
0
2
Order By: Relevance
“…It is obvious that one of the main ways to increase the efficiency of straw mineralization is the addition of mineral nitrogen to the soil [9]. Moreover, since the number of cellulolytic microorganisms in the soil is usually small [10], the process of straw destruction can be accelerated by introducing active strains of cellulolytics [11]. The results of the study showed that in the presence of ammonium nitrate (1% of the mass of plant residues), the process of decomposition of straw is activated (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…It is obvious that one of the main ways to increase the efficiency of straw mineralization is the addition of mineral nitrogen to the soil [9]. Moreover, since the number of cellulolytic microorganisms in the soil is usually small [10], the process of straw destruction can be accelerated by introducing active strains of cellulolytics [11]. The results of the study showed that in the presence of ammonium nitrate (1% of the mass of plant residues), the process of decomposition of straw is activated (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…На их основе создан ряд биопрепаратов, которые показали свою эффективность в борьбе с болезнями зерновых, бобовых, плодовых, цитрусовых, овощных культур, картофеля, винограда и др. [3][4][5][6][7][8][9][10][11].…”
Section: Introductionunclassified
“…Комплексные инокулянты широкого спектра действия на основе ассоциаций микроорганизмов оказывают стабильное положительное действие на растения и почвенную микробиоту и могут быть успешными элементами интегрированных систем защиты растений от возбудителей болезней и вредителей [11][12][13].…”
Section: Introductionunclassified